Pengaruh Gaya Kepemimpinan terhadap Loyalitas Karyawan Departemen Housekeeping di Hotel Furamaxclusive Resort and Villas Ubud - Ni Desak Made Santi Diwyarthi; Nyoman Gede Mas Wiartha; I Wayan Jata; Anak Agung Aditya Priambada (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Employee loyalty reflects the commitment of employees to their company, fostering a sense of responsibility and belonging. It goes beyond simply staying with the organization; it involves employees feeling integrated within the company, which helps them maximize their performance. One key factor influencing employee loyalty is leadership style. The effectiveness of any leadership style depends greatly on the situational context in which it is applied. Therefore, understanding how leadership style impacts employee loyalty is essential. This research identified specific elements of leadership style that negatively and significantly affect employee loyalty at Furamaxclusive Resort and Villas Ubud. The study found that leadership style accounts for 56.1% of employee loyalty, indicating a substantial influence. However, 43.9% of the variance in employee loyalty is attributed to other factors that were not explored in this study. In conclusion, while leadership style plays a major role in fostering employee loyalty, organizations should also consider other factors such as work environment, career development, and employee recognition to enhance overall loyalty. Addressing these elements holistically can result in more loyal and dedicated employees.